The challenges of innovation for sustainable agriculture and rural development: Integrating local actions into European policies with the Reflective Learning Methodology. Issue 4 (December 2014) - Moschitz, Heidrun; Home, Robert
The linear view of innovation in agricultural contexts is being replaced by systems approaches. Agricultural producers are seen as important actors rather than merely consumers of the technologies that are generated by agricultural research and transferred by education and extension services for subsequent adoption. This new understanding of innovation for sustainable agriculture is however not reflected within the European policy framework, so learning and innovation networks for sustainable agriculture (LINSA) have formed in response. The support needs of these innovation networks are poorly understood which hampers their integration into policy. A participatory action research approach – the Reflective Learning Methodology was developed and applied to address the challenge of up-scaling from local learning and innovation networks to a regional, in this case European, support framework for innovation in sustainable agriculture. We examine the Reflective Learning Methodology by describing and analysing its application in a European level action research project. This approach involves identifying some of the challenges of transdisciplinary research and finding ways of addressing them and critically reflecting on the role of the researcher in participatory action research. With the Reflective Learning Methodology, we have developed a tool, which has the potential to be adapted to research projects in other contexts.